The Enhancing Cement Strength through Utilization of Rice Husk Ash (RHA) Additive: An Experimental Study - Novia Rita; Novrianti Novrianti; Adi Novriansyah; Muhammad Ariyon (Universitas Islam Riau (UIR) Press, 2018)
Designing a slurry with adequate strength resistance is a major objective in oil and gas completion job. Various studies and research confirms that Compressive Strength (CS) and Shear Bond Strength (SBS) are two parameter which is imperative in describing cement strength in well cementing job. This experimental study introduces a Rice Husk Ash (RHA), an alternative cement additive derived from organic waste. RHA rich in silicon oxide (SiO2) and has a pozzolanic reaction, which is correlated in enhancing cement strength. Serial cement samples with various concentration of RHA were prepared to investigate the effect of RHA concentration to CS and SBS. All samples were then Dried for 24 hours in room condition after completing mixing and molding process. A Biaxial Loading test was then performed to all samples to determine the CS and SBS values by using hydraulic press apparatus. Results from the loading test generally indicate an enhancement of CS and SBS for samples with 31%, 32%, 33%, and 34% RHA. An indication of higher CS and SBS is not found for sample with 35% RHA, comparing with 34% RHA. Thus, 34% RHA is the optimum concentration for theses study, which yield 1312. psi of CS and 158.16 psi of SBS. Through this study, there is an opportunity for transforming waste material into alternative additive with higher economic value.